Prostate cancer diagnostics - new perspectives for salivary and urinary biomarkers - Łapiński, Maciej; Lewkowska, Monika; Sadowska, Maja (Journal of Education, Health and Sport, 2025)
Background. The growing epidemiological burden of prostate cancer, projected for 2025, combined with the diagnostic limitations of prostate-specific antigen (PSA), necessitates the search for new strategies in precision oncology. Aim. This review article analyzes the evolution of diagnostic methods, pointing to the need to move from traditional serum markers to non-invasive liquid biopsy. Material and methods. We synthesize the current state of knowledge on established urinary biomarkers and present a novel approach using saliva as a source of information on cancer status. Results. The paper discusses the potential of metabolic profiling (sialic acid, citrate), identification of new protein biomarkers (S100P), analysis of specific microRNA signatures depending on the stage of the disease, and the role of the oral microbiome in pathogenesis and risk stratification. Conclusions. We conclude that salivary and urinary biomarkers represent a rapidly developing experimental direction in prostate cancer diagnostics. Preliminary studies indicate promising diagnostic performance; however, the majority of available evidence is based on pilot and case–control studies and requires further large-scale validation before clinical implementation.